DIGITALISASI MANAJEMEN KEUANGAN UMKM SASAKA DONUT DI KOTA MATARAM MELALUI PENERAPAN APLIKASI KASIR PINTAR - Akbar Tawaqqal; Leni Agustina; Ni Kadek Kanaka Arta Putri; Fendri Sheva Ziljian; Baiq Naya Zalfani; Ahmad Anshari Asiddiqi; Fikrihadi Kurnia (Universitas Mataram, 2026)
The strategic role of Micro, Small, and Medium Enterprises (MSMEs) as the engine of the national economy is frequently hindered by a lack of financial literacy, particularly amidst the rapid wave of digitalization. Consequently, this community service program was organized with the primary objective of escalating the managerial capacity of Sasaka Donut, an MSME based in Mataram City. The intervention focused on restructuring financial governance to operate systematically, transparently, and efficiently through the deployment of the Kasir Pintar Point of Sale (POS) application. A descriptive qualitative approach grounded in the Asset-Based Community Development (ABCD) method was employed throughout the program. This methodology facilitated the participatory involvement of the partner across five essential stages: planning, analysis, design, implementation, and final evaluation. Field findings demonstrate that the transition to a digital ecosystem successfully eliminated the constraints of manual bookkeeping and resolved the overlapping issue between personal and operational funds. During the post-training observation phase (November 15-30, 2025), the system automatically documented 74 transactions, accumulating a total revenue of IDR 65,272,000, and provided real-time net margin calculations. Further SWOT analysis confirmed that technology adoption not only mitigates the risk of human error but also establishes a precise analytical foundation for Data-Driven Decision Making, a crucial pillar for ensuring long-term business sustainability and expansion